Cooperative bargaining of Australian coal plants under a regulatory threat - Rolli, Justin (2017)
The energy market in Australia and particularly the state of Victoria, finds itself in a precarious, transitional state. Researchers have concluded that barriers to orderly exit are present for highly-polluting and aged incumbent brown coal generation, further preventing renewable generation from entering the market (Riesz & Noone, 2013; AEMC, 2015a; Frontier Economics, 2015). Faced with oversupply of generating capacity and the unwillingness of the government to adopt a first-best carbon price, a variety of second-best measures have emerged attempting to achieve an emissions-efficient retirement and help Australia reach its ratified emission targets (Caldecott et al., 2015; Jotzo & Mazouz, 2015; Nelson et al., 2015). This paper aims to investigate the usefulness of a cooperative bargaining mechanism under the threat of an emissions performance standard (EPS), for two of the most emission intensive generators in the National Electricity Market. We estimate the expected income for the generators over their expected lives under differing EPS stringencies from a base case scenario. Utilising Nash Bargaining, it is determined whether an agreement can be reached for one to pay the other to retire. The power plants choose between lowering output (‘mothballing’ capacity), or installing carbon capture and storage facilities (CCS) in order to comply with the regulation. We finally introduce expectations of regulatory uncertainty to examine the effect on previous outcomes. The findings indicate that implementing a modest but credible threat of a 1.1t CO2-e/MWh could theoretically achieve a plant exit. High decommissioning and rehabilitation costs prevent weaker and more politically acceptable emission standards succeeding. The owners select mothballing of capacity over the high investment costs and inefficiencies associated with CCS to adhere to the regulation when bargaining fails. When introducing regulatory uncertainty with the outcome, the agreement is expected to fail if plant owners expect the policy to be ineffective on profits for more than 51% of the time.